Alpha‐calcitonin gene‐related peptide prevents pressure‐overload induced heart failure: role of apoptosis and oxidative stress - Ambrish Kumar; Scott Supowit; Jay D. Potts; Donald J. DiPette (Physiological Reports, 2019)
Abstract Alpha‐calcitonin gene‐related peptide (α‐CGRP) is a 37‐amino acid neuropeptide that plays an important protective role in modulating cardiovascular diseases. Deletion of the α‐CGRP gene increases the vulnerability of the heart to pressure‐induced heart failure and the administration of a modified α‐CGRP agonist decreases this vulnerability. Systemic administration of α‐CGRP decreases blood pressure in normotensive and hypertensive animals and humans. Here we examined the protective effect of long‐term administration of native α‐CGRP against pressure‐overload heart failure and the likely mechanism(s) of its action. Transverse aortic constriction (TAC) was performed to induce pressure‐overload heart failure in mice. We found that TAC significantly decreased left ventricular (LV) fractional shortening, ejection fraction, and α‐CGRP content, and increased hypertrophy, dilation, and fibrosis compared to sham mice. Administration of α‐CGRP‐filled mini‐osmotic pumps (4 mg/kg bwt/day) in TAC mice preserved cardiac function and LV α‐CGRP levels, and reduced LV hypertrophy, dilation, and fibrosis to levels comparable to sham mice. Additionally, TAC pressure‐overload significantly increased LV apoptosis and oxidative stress compared to the sham mice but these increases were prevented by α‐CGRP administration. α‐CGRP administration in TAC animals decreased LV AMPK phosphorylation levels and the expression of sirt1, both of which are regulatory markers of oxidative stress and energy metabolism. These results demonstrate that native α‐CGRP is protective against pressure‐overload induced heart failure. The mechanism of this cardio‐protection is likely through the prevention of apoptosis and oxidative stress, possibly mediated by sirt1 and AMPK. Thus, α‐CGRP is a potential therapeutic agent in preventing the progression to heart failure, and the cardio‐protective action of α‐CGRP is likely the result of a direct cellular effect; however, a partial vasodilatory blood pressure‐dependent mechanism of α‐CGRP cannot be excluded.